FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN KERJA PERAWAT DI RUANG RAWAT INAP RSUD HAJI BOEJASIN PELAIHARI - Herawati; Sirait, Elprida; Pertiwiwati, Endang (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2016)
Job satisfaction is an individual person's general attitude towards the work he does. A personwith a high level of job satisfaction showed a positive attitude towards work, while someone whois not satisfied with his work showed a negative attitude towards his job. This study was aimed toexamine the factors (payment, employment, promotion, supervision, colleagues, leadership, andcommunication) that affect job satisfaction of nurses. The study design was cross-sectionaldescriptive. The research instrument in the form of a questionnaire. The study was conductedfrom August 2015 to November 2015 at 83 nurses respondent in Haji Boejasin Pelaiharihospitals. Data analysis used the Fisher Exact. The results showed that only occupational factorswas not associated with job satisfaction (p value 0.302), while other factors related. Advised tomake improvements to the factors that affect job satisfaction of nurses to maximize employment.